(untitled) (JOURNAL OF ADVANCES IN CHEMISTRY, 2016)
Crystalline Ceramic Lanthanum Zirconium Yttrium barium Calcium Copper oxide(L0.1ZY0.9BCCO)Â was prepared by a high-energy ball milling process through mechanically assisted synthesis at a high temperature to acquire the desired homogeneity and phase formation. Inorder to study the optical properties like reflectivity, absorptivity, refractive index, the UV-VIS analysis of the above nonstochiometric sample was carried out. The dispersion of refractive index was analyzed by the Wemple-DiDomenico single-oscillator model.The band gap energy of the sample was elucidated from the Tauc plot. The refractive index n was calculated andÂ the results obtained are plottedÂ with the wavelength.Â